2021
DOI: 10.1038/s41598-021-02907-7
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent inductance model for the design analysis of electrodynamic suspension coils for hyperloop

Abstract: Hyperloop is a new concept of ground transportation. In Hyperloop, travelling occurs in near-vacuum tubes under 0.001 atm at a subsonic speed of up to 1200 km/h. During acceleration to and driving at a subsonic speed, magnetic levitation is employed. Thus far, various levitation technologies in existing high-speed maglev trains have been considered. Among those technologies, superconducting (SC) electrodynamic suspension (EDS) is a highly effective levitation system for Hyperloop owing to its advantages of a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Electromagnetic suspension system (EMS) and Electrodynamic suspension system (EDS) are two of such systems, which are ascertained as suitable for Hyperloop design. [6][7][8][9][10] Extensive research has been reported to make these compatible with the Hyperloop environment. The EMS uses magnetic effects to maintain a levitation gap.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic suspension system (EMS) and Electrodynamic suspension system (EDS) are two of such systems, which are ascertained as suitable for Hyperloop design. [6][7][8][9][10] Extensive research has been reported to make these compatible with the Hyperloop environment. The EMS uses magnetic effects to maintain a levitation gap.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from its superiority of the contactless, frictionless, and noiseless, magnetic levitation system has been successfully applied to many fields 1 , 2 , such as high-speed maglev trains 3 , maglev wind turbines 4 , and frictionless magnetic bearings 5 . With the open-loop unstable and inherent nonlinear characteristics, it is a constant challenge to design the high-performance control scheme for position control of the magnetic levitation system 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%